2014
DOI: 10.1186/2251-6581-13-7
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum level of vitamin D and lipid profiles in type 2 diabetic patients in Iran

Abstract: BackgroundIt is suggested that vitamin D deficiency is associated with cardiovascular disease (CVD) via its effect on lipid profiles. The objective of this study was to determine the association between fasting serum levels of 25(OH) D and lipid profiles in patients with type 2 diabetes.MethodsThis cross-sectional study was conducted on 108 type 2 diabetics. Patients were selected randomly among members of the Iranian Diabetes Association according to study criteria. Fasting concentration of 25(OH) D, calcium,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
42
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 34 publications
8
42
4
Order By: Relevance
“…18 Vitamin D regulates triglyceride metabolism by causing the expression of VLDL cholesterol receptors in some types of cells. 19 Our study showed positive association between 25-hydroxy vitamin D and LDL cholesterol in ischemic stroke patients similar to a study on diabetics in Iran by Saedisomeolia A et al 20 Grimes D et al suggested that in the presence of sunlight squalene is converted to 7-dehydrocholesterol and vitamin D and in the absence of sunlight it is diverted to the synthesis of cholesterol. 21 Positive association was found between 25-hydroxy vitamin D and the ratio of low-density lipoprotein to high-density lipoprotein in our study whereas in a prospective study by Carbone LD et al significant negative correlation was found between 25-hydroxy vitamin D and the ratio of low-density lipoprotein to high-density lipoprotein.…”
Section: Methodssupporting
confidence: 72%
“…18 Vitamin D regulates triglyceride metabolism by causing the expression of VLDL cholesterol receptors in some types of cells. 19 Our study showed positive association between 25-hydroxy vitamin D and LDL cholesterol in ischemic stroke patients similar to a study on diabetics in Iran by Saedisomeolia A et al 20 Grimes D et al suggested that in the presence of sunlight squalene is converted to 7-dehydrocholesterol and vitamin D and in the absence of sunlight it is diverted to the synthesis of cholesterol. 21 Positive association was found between 25-hydroxy vitamin D and the ratio of low-density lipoprotein to high-density lipoprotein in our study whereas in a prospective study by Carbone LD et al significant negative correlation was found between 25-hydroxy vitamin D and the ratio of low-density lipoprotein to high-density lipoprotein.…”
Section: Methodssupporting
confidence: 72%
“…In addition, triglycerides (β=-1.868, P=0.009) was found to be an independent factor negatively associated with serum 25(OH)D in the present study. Similar inverse associations between serum 25(OH)D levels and triglycerides were also documented by other studies [33,34]. The potential biological mechanism underlying this relation is still not completely understood but may be mediated, in part, by the effects of dietary calcium [35].…”
Section: Discussionsupporting
confidence: 67%
“…In the present study, hypovitaminosis D was 11 times more common in individuals with high concomitant levels of LDL-c and TG compared to no change in these factors and much more frequently than in the presence of these factors alone (OR TG = 2.1; OR LDL-c = 3.5). Vitamin D appears to have an effect on the regulation of lipid profile and is considered by some authors as one of the mechanisms that explain its relationship with the DCV [44]. Some observational studies claim that low levels of vitamin D are associated with an unfavorable lipid profile [14], but some clinical studies do not confirm these findings [14].…”
Section: Discussionmentioning
confidence: 69%